Immune checkpoint inhibitors for patients with microsatellite instability-high colorectal cancer: protocol of a pooled analysis of clinical trials - Tang, Xiaojun; Xu, Xinshu; Chen, Ruobing; Zhang, Mengmeng; Mei, Zubing; Zhang, Shuangxi (Frontiers in Oncology, 2024)
Introduction Colorectal cancer (CRC) is the third most common cause of cancer and the second leading cause of cancer-related deaths worldwide. Microsatellite instability-high (MSI-H) is a distinct molecular subtype of CRC that occurs in approximately 15% of all cases. Recently, immune checkpoint inhibitors (ICIs) have emerged as a promising therapeutic approach for patients with MSI-H colorectal cancer, exhibiting higher response rates than standard chemotherapies. To assess the effectiveness and safety of ICIs for the treatment of patients with MSI-H CRC, we propose a comprehensive pooled analysis of clinical trial data. Methods and analysis A systematic search of multiple electronic databases, including PubMed, EMBASE, Cochrane Library, and Clinicaltrials.gov, will be conducted from their inception until September, 2023 to identify eligible randomized controlled trials (RCTs) and non-randomized studies. Inclusion criteria comprise studies of adult patients with histologically confirmed MSI-H CRC treated with immune checkpoint inhibitors, with a comparison to a control group receiving conventional therapies. Outcomes of interest will be overall survival (OS), progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), and incidence of treatment-related adverse events (AEs). The Cochrane Risk of Bias tool and the Risk of Bias in Non-randomized Studies of Interventions (ROBINS-I) tool will be employed to evaluate the methodological quality of included studies. A random-effects model using the DerSimonian and Laird method will be applied for pooling the effect estimates, calculating hazard ratios (HRs) or risk ratios (RRs) with their corresponding 95% confidence intervals (CIs). Heterogeneity will be assessed using I² statistics, and subgroup analysis and meta-regression will be performed to explore potential effect modifiers in case of substantial heterogeneity. Publication bias will be evaluated with funnel plots and Egger’s test. Sensitivity analysis will be conducted to assess the robustness of the results. Discussion This meta-analysis will synthesize available evidence from clinical trials on immune checkpoint inhibitors in treating MSI-H colorectal cancer. The findings will offer valuable information about the effectiveness and safety of ICIs in this patient population, contributing to the refinement of clinical guidelines and enhancing the decision-making process for healthcare providers, policy-makers, and patients. The comprehensive analysis of subgroups and sensitivity allows for an in-depth understanding of potential effect modification, providing essential directions for future research. Ethics and dissemination This study will involve the use of published data; hence, ethical approval is not required. The results of the study will be disseminated through publications in peer-reviewed journals and presentations at relevant conferences. The findings will potentially impact clinical decision-making and contribute to the development of evidence-based treatment recommendations for patients with MSI-H colorectal cancer. Clinical trial registration Open Science Framework identifier, 10.17605/OSF.IO/ZHJ85